Mothers’ Partnership Instability and Coparenting among Fragile Families - Cooper, Carey E. (Soc Sci Q, 2015)
OBJECTIVES: The rise in nonmarital childbearing has raised concerns about coparenting among unmarried parents with increasingly complicated relationship trajectories. We address this issue by examining associations between mothers’ partnership transitions and coparenting and the moderating role of maternal race/ethnicity and child gender. METHODS: Data from the Fragile Families Study and ordinary least squares regression techniques are used to examine whether mothers’ partnership transitions are related to coparenting. Lagged and fixed effects models are employed to test the robustness of the findings to selection. RESULTS: Coresidential and nonresidential, dating transitions are negatively associated with coparenting, but the association is stronger for coresidential transitions than for dating transitions. Coresidential transitions are stronger predictors of coparenting for White parents than for Black parents and for parents of sons than for parents of daughters. CONCLUSIONS: Policies aimed at strengthening families should emphasize relationship stability, regardless of the type of union, to promote high quality coparenting among at-risk populations.